Genetic Regulation of the Growth Plate - Karimian, Elham; Chagin, Andrei S.; Sävendahl, Lars (Frontiers in Endocrinology, 2012)
The epiphyseal growth plate consists of a layer of cartilage present only during the growth period and vanishes soon after puberty in long bones. It is divided to three well defined zones, from epiphyses; resting, proliferative and hypertrophic zones. Chondrocyte proliferation and differentiation and subsequent bone formation in this cartilage are controlled by various endocrine, autocrine and paracrine factors which finally results into elimination of the cartilaginous tissue and promotion of the epiphyseal fusion. As chondrocytes differentiate from round, quiescent and single structure to flatten and proliferative and then large and terminally differentiated, they experience changes in their gene expression pattern which allow them to transform from cartilaginous tissue to bone. This review summarizes the literature in this area and shortly describes different factors that affect growth plate cartilage both at the local and systemic levels. This may eventually help us to develop new treatment strategies of different growth disorders.